-m/9=1

Simple and best practice solution for -m/9=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m/9=1 equation:


m in (-oo:+oo)

-m/9 = 1 // - 1

-m/9-1 = 0

-1/9*m-1 = 0 // + 1

-1/9*m = 1 // : -1/9

m = 1/(-1/9)

m = -9

m = -9

See similar equations:

| (X-46)+(x+4)=90 | | 32x+40y=1200 | | 0.2k=-15 | | 30x=9 | | 2a(a-1)(3a-1)=0 | | 80x=-60 | | -7y-4=-3(y-4) | | -t/7=2 | | 12/4*2-7 | | X+156=154 | | 67+x(.25)=85 | | 12/y=3/4 | | g(-1/2)=2(-1/2)-3 | | 3(v-5)=39 | | 6x-15/2x-5 | | 13x-7=11x+3 | | 3(v-5)=9 | | Y-17=-28 | | 12+5x=-2x+61 | | -4r+5r=r | | V-v+4v=4 | | 4/x-3.4=17 | | 4x-9=3forx | | 1/4z=1 | | 3x-4=12-10 | | 15k-14k-1=13 | | 8m+24=-3m+3 | | 25+(x-5)=90 | | 4w-2w=20 | | 9/3-4*5 | | 20m-19m=2 | | 12x+4x=12 |

Equations solver categories